Effect of grain-sorting waves on alternate bar dynamics: implications of the breakdown of the hydrograph boundary layer - S. Tanabe; T. Iwasaki (Earth Surface Dynamics)
Understanding the morphological responses of gravel-bed rivers to changes in external forces (e.g. water and sediment supply conditions) is a critical concern in river science and engineering. However, this remains challenging because river responses depend heavily on the distance from the source point where such environmental changes occur. In this study, we focus on the short-term effects of flood-scale non-equilibrium sediment supply on downstream alternate bar dynamics in poorly sorted gravel-bed rivers using a numerical morphodynamic model. Specifically, a two-dimensional morphodynamic calculation was performed using iRIC-Nays2DH in a straight channel under repeated cycles of an unsteady water hydrograph and a constant supply of poorly sorted sediment. In well-sorted sediment cases, the upstream non-equilibrium sediment supply only affects a limited distance from the upstream end (i.e. the hydrograph boundary layer). However, the inclusion of poorly sorted sediment disrupts this concept and leads to the migration of low-amplitude bedload sheets farther downstream. In this context, the upstream water and sediment boundary conditions may affect far-downstream river dynamics through the migration of bedload sheets. The numerical results showed that the migration of bedload sheets and the associated fine sediment transport substantially affected the alternate bar dynamics and changed their texture. However, this effect of bedload sheets on the bars cannot propagate along the entire channel and disappears completely in alternate bars located further downstream. These results suggest that upstream non-equilibrium sediment supply conditions in poorly sorted sediment play a major role in downstream alternate bar dynamics. However, this effect becomes negligible further downstream because bedload sheets gradually disperse during their migration process into larger and more active morphological features, such as alternate bars.